Exploring functionalized polythiophene derivatives based on thiophene-linker-thiophene platform, analysis of prototype monomer crystal for CBr/CH bulk polycondensation and its application for acid detection. (2nd April 2019) - Jiang, Kang; Cai, Xinyi; Liu, Xinghai; Xia, Jiangbin
Abstract: Ten thiophene derivatives monomers were designed based on thiophene-linker-thiophene platform and were subjected to CBr/CH bulk polycondensation. All of them were converted to corresponding polythiophene derivatives smoothly, indicating that up to three-building-blocks of thiophene monomers can be successfully constructed. Detailed characterizations of the obtained polymers were carried out by regular measurements, including Cyclic Voltammetry (CV), Infrared spectrum (IR), UV–Vis absorbance spectroscopy, TGA and so on. In addition, the obtained poly{phenyl-bis-(4-thiophen-2-yl-phenyl)-amine} was employed as acid sensor and the results showed that HNO3 acid could be recognized and distinguished successfully. Furthermore, a prototype monomer crystal of 2-bromo-3-(9, 9-dimethyl-9H-fluoren-2-yl)-thiophene is obtained and its effective reaction points distance (4.197 Å) is longer (37.6%) than the van der Waals radius (rw ) of reaction points (sum of rw of bromine and hydrogen atoms 3.05 Å). Graphical abstract: Several non active thiophene monomers were designed based on Thiophene-linker-Thiophene platform and investigated under CBr/CH polycondenstion. All of them converted to corresponding polythiophene derivatives smoothly, indicating that three building blocks can be constructed in CBr/CH polycondensation. In addition, poly (bithiophene-triphenylamine) was employed as acid sensor and HNO3 was recognized successfully.Image 1 Highlights: Three-building-blocks of thiophene monomers can be polymerized through CBr/CH bulk polycondensation. A prototype monomer crystal of 2-bromo-3-(9, 9-dimethyl-9H-fluoren-2-yl)-thiophene is obtained for CBr/CH bulk polycondensation. Poly{phenyl-bis-(4-thiophen-2-yl-phenyl)-amine} was employed as HNO3 acid sensor.